2011
DOI: 10.1016/j.ab.2011.06.030
|View full text |Cite
|
Sign up to set email alerts
|

A vertically stacked, polymer, microfluidic point mutation analyzer: Rapid high accuracy detection of low-abundance K-ras mutations

Abstract: Recognition of point mutations in the K-ras gene can be used for the clinical management of several types of cancers. Unfortunately, several assay and hardware concerns must be addressed to allow users not well-trained in performing molecular analyses the opportunity to undertake these measurements. To provide for a larger user-base for these types of molecular assays, a vertically-stacked microfluidic analyzer with a modular architecture and process automation was developed. The analyzer employed a primary PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…This finding has significant implications as it is becoming increasingly apparent that cancer cells within a tumor show extensive genetic and phenotypic heterogeneity, thus rendering the design of effective therapies that target all cell populations within tumors a major challenge. The existence of such heterogeneity in tumors harboring mutant KRAS is indicated by reports demonstrating significant variations in KRAS mutational status in lung, colon, and papillary thyroid carcinomas (Baldus et al, 2010; Dieterle et al, 2004; Han et al, 2011; Perez et al, 2013; Richman et al, 2011). Importantly, it has been shown that mutant KRAS clones can affect the chemosensitivity of non-mutant KRAS clones rendering them resistant to anti-cancer therapies (Hobor et al, 2014; Molinari et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This finding has significant implications as it is becoming increasingly apparent that cancer cells within a tumor show extensive genetic and phenotypic heterogeneity, thus rendering the design of effective therapies that target all cell populations within tumors a major challenge. The existence of such heterogeneity in tumors harboring mutant KRAS is indicated by reports demonstrating significant variations in KRAS mutational status in lung, colon, and papillary thyroid carcinomas (Baldus et al, 2010; Dieterle et al, 2004; Han et al, 2011; Perez et al, 2013; Richman et al, 2011). Importantly, it has been shown that mutant KRAS clones can affect the chemosensitivity of non-mutant KRAS clones rendering them resistant to anti-cancer therapies (Hobor et al, 2014; Molinari et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the modular approach, each device or component is developed separately and connected by fluidic interconnects to build a fluidic system [22]. Modular micro- and nanofluidic systems provide flexibility in design and fabrication enabling device-specific material selection and the ability to add additional functions, or extra options, to enhance system performance [23,24]. In addition, each device or component, although designed for one application, may be used for other applications.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of point mutations in the K-ras gene of the human genome with the ligase detection reaction (LDR) preceded by PCR, shown schematically in the Supplemental Information, was selected as a demonstration of the vertically stacked system [46,47]. Several different configurations of microfluidic modules for executing the assay were assembled with two, one comprised of three steps and the other four, characterized in detail biochemically [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The assays are designed to allow for multiplexing, yet have the convenience of a qPCR readout, which is amenable to detection using commercial instruments, or in the future, automation using microfluidic devices (Dharmasiri et al, 2011; Hashimoto, Barany, & Soper, 2006; Hashimoto, Barany, Xu, & Soper, 2007; Hashimoto et al, 2005; Sinville et al, 2008; Situma et al, 2005; Soper et al, 2005; Wang et al, 2003). Ligation‐based mutation detection technology, such as ligase detection reaction (LDR), has been successfully implemented to detect low‐abundance mutations (Albrecht, Kotani, Lin, Soper, & Barron, 2013; Barany, 1991; Gerry et al, 1999; Han, Lee, Nikitopoulos, Soper, & Murphy, 2011; Hashimoto et al, 2006). One advantage of using PCR‐LDR‐qPCR is the ability to perform proportional PCR amplification of multiple fragments to enrich for low copy targets and subsequently use LDR followed by qPCR detection of the ligation products to identify cancer‐specific mutations.…”
Section: Introductionmentioning
confidence: 99%